Advancements in Medical Laser Technologies for Targeted Cancer Treatment: A New Era in Precision Oncology - Nasser, Mohammed Khudhur Ali; Badawi, Abbas Daim Enaad; Safouk, Samaher Hisham Ayed; Rashid, Lubna abdul kareem; Tareen, Haitham Nouri Anad (American Journal of Botany and Bioengineering, 2025)
Advancements in medical laser technologies have revolutionized cancer treatment, offering precision-targeted therapies with minimal invasiveness. Despite significant progress, challenges remain in optimizing laser-tissue interactions for enhanced efficacy and safety. This study reviews the latest innovations in medical laser applications for oncology, focusing on their mechanisms, effectiveness, and integration with imaging technologies. Findings reveal that laser-based therapies improve tumor ablation, reduce recovery times, and minimize damage to surrounding healthy tissues. The results highlight the growing role of lasers in precision oncology, emphasizing the need for further research to enhance treatment personalization and accessibility. These advancements underscore the potential of laser technologies to transform cancer treatment, offering a promising alternative to conventional therapeutic approaches.